2018
DOI: 10.3389/fped.2018.00378
|View full text |Cite
|
Sign up to set email alerts
|

Canonical WNT/β-Catenin Signaling Plays a Subordinate Role in Rhabdomyosarcomas

Abstract: The development of skeletal muscle from immature precursors is partially driven by canonical WNT/β-catenin signaling. Rhabdomyosarcomas (RMS) are immature skeletal muscle-like, highly lethal cancers with a variably pronounced blockade of muscle differentiation. To investigate whether canonical β-catenin signaling in RMS is involved in differentiation and aggressiveness of RMS, we analyzed the effects of WNT3A and of a siRNA-mediated or pharmacologically induced β-catenin knock-down on proliferation, apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…In our work on RMS, the observed increase in β-catenin expression and the promotion of its nuclear location, both observed after genetic or pharmacological DKK-1 inhibition, did not produce significant variations in the canonical target c-Myc. This result is in agreement with previous observations that point out a relevance of the non-canonical Wnt signaling pathway in RMS [ 23 , 24 ]. However, the consistent activation of myogenic markers such as MYOD1 and myogenin, together with the reduction of FAK expression, suggests the triggering of a coordinated anti-oncogenic response.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our work on RMS, the observed increase in β-catenin expression and the promotion of its nuclear location, both observed after genetic or pharmacological DKK-1 inhibition, did not produce significant variations in the canonical target c-Myc. This result is in agreement with previous observations that point out a relevance of the non-canonical Wnt signaling pathway in RMS [ 23 , 24 ]. However, the consistent activation of myogenic markers such as MYOD1 and myogenin, together with the reduction of FAK expression, suggests the triggering of a coordinated anti-oncogenic response.…”
Section: Discussionsupporting
confidence: 94%
“…Despite the effects on proliferation and myogenic markers observed in vitro, genetic inhibition or treatment with WAY-262611 did not produce significant effects on tumor growth in the primary mouse models. These results coincide with a previous work where they show that reactivation of the β-catenin pathway did not produce significant effects on proliferation in a RMS in vivo model [ 23 ]. Indeed, it has been described that activation of Wnt/β-catenin signaling produces differentiation of RMS cells without a clear effect in proliferation and/or apoptosis [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…In order to verify the protective mechanism of LE, which increased Wnt1, we were required to interrupt the protective process. XAV939, a Wnt/β-catenin signaling pathway inhibitor, has been commonly utilized to inhibit Wnt activity in many studies [ 45 , 46 ]. In the present study, the i.p.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the relevance and potential for clinical intervention in the Wnt pathway in ARMS remains highly controversial [204]. So far, a single study by Annavarapu et al found an inhibition of proliferation and self-renewal capacity after pharmacological re-activation of the Wnt pathway in vitro [205].…”
Section: Wnt/β-catenin Pathwaymentioning
confidence: 99%